Factors Impacting Ethical Behavior in a Chinese State-Owned Steel Company - Fu, Weihui; Deshpande, Satish P. (2012)
This study examines factors impacting ethical behavior of 208 employees of a Chinese state-owned steel company. Only rules climate had a significant impact on ethical behavior of respondents. Other ethical climate types such as professional, caring, instrumental, independence, and efficiency did not impact ethical behavior of respondents. Ethical behavior of peers, ethical behavior of successful managers, and overclaiming had a significant impact on ethical behavior of subjects.
Keywords: Steel company; Overclaiming; Ethical Climate; Ethical Behavior; China